Edukasi Investasi Digital Profits Anywhere sebagai Literasi Keuangan dan Perlindungan Hukum di SMA Negeri 2 Penajam Paser Utara - Adi Prautomo; Nayla Shafa Kamila; Chandra Ryaldi Syahputra (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The development of digital technology has increased students' access to investment information and platforms, but this has not been matched by an understanding of risks, legality, and legal protection. This situation has the potential to create vulnerability to illegal investment practices. This community service activity aims to improve students' digital financial literacy and legal awareness through digital investment education utilizing the Profits Anywhere application. This application serves as a learning medium that provides stock transaction simulations, market movement monitoring, and investment information for beginners. The method used is an educational-participatory approach through material delivery, application simulations, discussions, and evaluation through quizzes and questionnaires. The activity results showed a 93.30% increase in understanding of digital investment and the legality of applications, a 95% increase in the ability to identify legal and illegal investment applications, and a 100% increase in awareness of risks and legal protection. These results indicate that application-based education is effective in improving students' financial literacy and legal awareness.